Heterogeneous multilayer composite polymer electrolyte and application thereof

By adopting a "sandwich" structure of heterogeneous multi-layer composite polymer electrolyte in polymer lithium metal batteries, combined with inorganic ceramics and additives, the problems of high impedance between the composite polymer electrolyte and the electrode interface and the formation of lithium dendrites are solved, and the electrochemical performance and stability of the battery are significantly improved.

CN119812454AInactive Publication Date: 2025-04-11NENGXIN (CHANGZHOU) ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202411951826.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are many challenges in the interface between the composite polymer electrolyte and the positive and negative electrodes, including high interface impedance, impeded ion transport, formation of lithium dendrites and the generation of harmful reactions, resulting in low electrochemical performance and unstable battery.

Method used

A heterogeneous multi-layer composite polymer electrolyte is used to form a "sandwich" structure through the combination of intermediate composite polymer electrolyte, negative electrode side polymer electrolyte and positive electrode side gel electrolyte, which improves the interface compatibility between the electrolyte and the electrode, and improves the ion conduction performance and lithium dendrites inhibition ability of the electrolyte through the addition of inorganic ceramics and additives.

Benefits of technology

It significantly improves the ion conduction performance of the electrolyte and the electrochemical performance of the battery, reduces the interface impedance, enhances the uniform precipitation of lithium ions and the long-term stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812454A_ABST
    Figure CN119812454A_ABST
Patent Text Reader

Abstract

The invention discloses a heterogeneous multilayer composite polymer electrolyte and application thereof, and belongs to the technical field of new energy materials, the heterogeneous multilayer composite polymer electrolyte is composed of an intermediate composite polymer electrolyte, a negative electrode side polymer electrolyte and a positive electrode side gel electrolyte, the middle composite polymer electrolyte is located between the negative electrode side polymer electrolyte and the positive electrode side gel electrolyte and is of a sandwich structure; the middle composite polymer electrolyte is composed of a polymer matrix A, a lithium salt and inorganic ceramic, the negative electrode side polymer electrolyte is composed of a polymer matrix B, a lithium salt and an additive, and the positive electrode side gel electrolyte is composed of a polymeric monomer, a lithium salt, a solvent and an additive. According to the invention, the interfacial compatibility between the composite polymer electrolyte and positive and negative electrodes is improved, and the interfacial ion transmission efficiency and the uniform precipitation of lithium ions are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials, and in particular relates to a heterogeneous multilayer composite polymer electrolyte and application thereof. Background Art

[0002] In the global context of environmental protection and sustainable development, the rapid development of electric vehicles and clean energy systems has put forward higher requirements for energy storage technology. Among them, polymer lithium metal batteries have become a key technology to promote the development of green energy and new energy vehicles by virtue of their safety and energy density that surpass traditional liquid lithium-ion batteries. As the core component of polymer lithium metal batteries, polymer electrolytes determine the actual performance of high-safety and high-energy-density batteries. Among them, composite polymer electrolytes combine inorganic ceramic conductors with organic polymer matrices, which not only improves the migration rate of ions, but also enhances the electrochemical stability and mechanical properties of polymer electrolytes, making them a strong candidate material for realizing high-safety and high-energy-density batteries.

[0003] Although the soft nature of composite polymer electrolytes helps to improve their interfacial contact with electrodes, high-safety and high-energy-density batteries based on such electrolytes still face many challenges at the electrolyte / electrode interface. First, the composite polymer electrolyte is still in solid-solid contact with the positive and negative electrodes, and pores or point contacts may be formed between the polymer matrix and the electrode surface. At the same time, the direct contact between the inorganic filler and the electrolyte cannot be completely eliminated, which increases the interface impedance and hinders ion transport, reducing the electrochemical performance. In addition, the volume change of the active material also puts forward requirements for the compatibility of the electrolyte / electrode interface. Moreover, unlike liquid electrolytes, composite polymer electrolytes cannot penetrate the voids inside the positive electrode, and fail to form sufficient interfacial contact, resulting in limited ion transport inside the positive electrode. For the interface between the lithium negative electrode and the composite polymer electrolyte, the main problem is the formation of lithium dendrites and the generation of harmful reactions. The composite polymer electrolyte cannot completely inhibit the formation and growth of lithium dendrites, and lithium dendrites may still bypass the rigid inorganic fillers and enter the polymer matrix. Moreover, due to the high reducibility of lithium, serious side reactions may occur at the interface, leading to the decomposition of the polymer matrix. Therefore, optimizing the interfacial contact between electrolyte and electrode and improving its ability to inhibit lithium dendrites are crucial to ensure the long-term stable operation of high-safety and high-energy-density batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a heterogeneous multilayer composite polymer electrolyte and its application. The present invention is conducive to improving the interface compatibility between the composite polymer electrolyte and the positive and negative electrodes, promoting the interface ion transmission efficiency and the uniform precipitation of lithium ions.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] The present invention provides a heterogeneous multilayer composite polymer electrolyte, which is composed of an intermediate composite polymer electrolyte, a negative electrode side polymer electrolyte and a positive electrode side gel electrolyte, wherein the intermediate composite polymer electrolyte is located between the negative electrode side polymer electrolyte and the positive electrode side gel electrolyte, forming a "sandwich" structure;

[0008] The intermediate composite polymer electrolyte is composed of polymer matrix A, lithium salt and inorganic ceramics, the negative electrode side polymer electrolyte is composed of polymer matrix B, lithium salt and additives, and the positive electrode side gel electrolyte is composed of polymer monomers, lithium salt, solvent and additives.

[0009] The polymer matrix A is selected from at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-chlorotrifluoroethylene (P(VDF-CTFE)), polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)), polyvinylidene fluoride-trifluoroethylene (P(VDF-TrFE)) and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene (P(VDF-TrFE-CTFE)); and / or

[0010] The polymer matrix B is polyethylene oxide (PEO); and / or

[0011] The polymerizable monomer is 1,3-dioxolane (DOL); and / or

[0012] The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), lithium hexafluorophosphate (LiPF6) and lithium difluorooxalatoborate (LiDFOB).

[0013] The mass ratio of the lithium salt to the polymer matrix A in the intermediate composite polymer electrolyte is 1:30-3:1; and / or

[0014] The mass ratio of the lithium salt in the negative electrode side polymer electrolyte to the polymer matrix B is 1:30-3:1; and / or

[0015] The mass ratio of the lithium salt to the polymer matrix in the positive electrode side gel electrolyte is 1:30-3:1.

[0016] The inorganic ceramic is selected from at least one of lithium germanium phosphosulfide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum cerium oxide, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium phosphosulfide, lithium lanthanum titanate, yttria-stabilized zirconium oxide, silicon dioxide, aluminum oxide, titanium dioxide and zirconium dioxide; and / or

[0017] The mass ratio of the inorganic ceramic to the polymer matrix A is 1:50-10:1.

[0018] The additive is selected from at least one of aluminum trifluoromethanesulfonate (Al(OTf)3), lithium tetrafluoroborate (LiBF4), zinc trifluoromethanesulfonate (Zn(OTf)2), tin trifluoromethanesulfonate (Sn(OTf)2), copper trifluoromethanesulfonate (Cu(OTf)2), silver trifluoromethanesulfonate (Ag(OTf)), indium trifluoromethanesulfonate (In(OTf)3), magnesium trifluoromethanesulfonate (Mg(OTf)2), stannous chloride (SnCl2), tin chloride (SnCl4), aluminum iodide (AlI3), aluminum fluoride (AlF3) and aluminum chloride (AlCl3); and / or

[0019] The concentration of the additive in the corresponding electrolyte is 0.0001-5 g / mL.

[0020] The solvent is selected from at least one of ethylene glycol dimethyl ether (DME), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE); and / or

[0021] The volume ratio of the solvent to the polymerization monomer is 1:10-10:1.

[0022] The present invention provides a heterogeneous multilayer composite polymer electrolyte, which improves the performance of the battery due to the improvement of the electrolyte performance and the improvement of the electrode / electrolyte interface compatibility. Specifically: the improvement of the electrolyte performance lies in the design of the intermediate composite polymer electrolyte, and its polymer matrix A has a relatively high dielectric constant, which helps to enhance the charge separation within the polar groups, thereby promoting the effective dissociation of lithium salts in the electrolyte, which helps to improve the ion conductivity of the electrolyte. In addition, the introduction of inorganic ceramics into the polymer matrix A can effectively reduce the crystallinity of the matrix, promote the mobility of the polymer chain, and thus significantly improve the ion conductivity of the electrolyte. The high strength of the inorganic ceramic can also effectively control the generation and growth of lithium dendrites during the battery cycle; the improvement of the electrode / electrolyte interface compatibility lies in the intermediate composite polymer electrolyte located between the polymer electrolyte on the negative electrode side and the gel on the positive electrode side. The "sandwich" structure formed between the electrolytes. At the negative electrode, the polymer matrix B of the polymer electrolyte on the negative electrode side is polyethylene oxide (PEO), which has good flexibility and can effectively achieve interfacial contact between the electrolyte and the electrode, reduce the interfacial impedance, and has good compatibility with lithium metal and its alloys; at the positive electrode, the gel electrolyte on the positive electrode side adopts an in-situ curing strategy to fully infiltrate the porous structure of the positive electrode, which helps to enhance the orderly migration of lithium ions, greatly reduce the interfacial impedance, and enhance the ion transfer efficiency. The added additives can also kill two birds with one stone. It is not only an in-situ curing initiator, but also can form an artificial SEI layer at the positive electrode to improve the uniformity of the lithium ion precipitation / stripping process.

[0023] The second technical solution of the present invention:

[0024] The present invention also provides an application of the heterogeneous multilayer composite polymer electrolyte in the preparation of a polymer lithium metal battery.

[0025] The third technical solution of the present invention:

[0026] The present invention provides a method for preparing a polymer lithium metal battery using the heterogeneous multilayer composite polymer electrolyte, comprising the following steps:

[0027] Adding lithium salt and inorganic ceramics to N,N-dimethylformamide, stirring evenly, then adding polymer matrix A, stirring evenly, obtaining A slurry with a solid content of 15-85%, scraping the A slurry on a support plate and drying, to obtain an intermediate composite polymer electrolyte;

[0028] Adding lithium salt and additives to acetonitrile, stirring evenly, then adding polymer matrix B, stirring evenly, obtaining B slurry with a solid content of 10-85%, scraping the B slurry on a support plate and drying, scraping the B slurry on a support plate and drying, to obtain a negative electrode side polymer electrolyte;

[0029] Hot pressing the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte to form a composite material, and assembling a battery, wherein one side of the negative electrode side polymer electrolyte in the composite material is in contact with the negative electrode;

[0030] Add lithium salt and additives to the solvent, stir evenly, then add polymerization monomer, stir evenly to obtain a positive electrode side gel electrolyte precursor solution, drop the positive electrode side gel electrolyte precursor solution between the positive electrode and the intermediate composite polymer electrolyte, and polymerize the positive electrode side gel electrolyte precursor solution to form a positive electrode side gel electrolyte to obtain the polymer lithium metal battery.

[0031] Furthermore, the thickness of the intermediate composite polymer electrolyte is 70-150 μm.

[0032] Furthermore, the thickness of the negative electrode side polymer electrolyte is 10-30 μm.

[0033] Furthermore, the method for preparing a polymer lithium metal battery using the heterogeneous multilayer composite polymer electrolyte is:

[0034] Add lithium salt and inorganic ceramics to N,N-dimethylformamide and stir for 1-12 hours, then add polymer matrix A and mix and stir for 5-36 hours to obtain A slurry with a solid content of 15-85%, then scrape the A slurry on a support plate and place it in a vacuum oven at a temperature of 30-100° C. for drying for 10-60 hours, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 70-150 μm;

[0035] Add lithium salt and additives to acetonitrile and stir for 1-12 hours, then add polymer matrix B and mix and stir for 1-36 hours to obtain B slurry with a solid content of 10-85%, then scrape the B slurry onto a support plate and place it in a vacuum oven at a temperature of 30-100° C. to dry for 10-60 hours, and cut it to obtain a negative electrode side polymer electrolyte with a thickness of 10-30 μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 40-80° C. and a pressure of 1-100 MPa for 1-120 minutes;

[0036] Add lithium salt and additives to the solvent and stir for 0.1-2h, then add polymerization monomer and mix and stir for 0.01-1h to obtain a positive electrode side gel electrolyte precursor solution, drop the positive electrode side gel electrolyte precursor solution between the positive electrode and the intermediate composite polymer electrolyte, and the positive electrode side gel electrolyte precursor solution is polymerized to form a positive electrode side gel electrolyte to obtain the polymer lithium metal battery.

[0037] The negative electrode is one of metallic lithium, lithium aluminum alloy, lithium silicon alloy, lithium copper alloy, lithium tin alloy, silicon carbon negative electrode, hard carbon negative electrode and graphite.

[0038] The active materials of the positive electrode are lithium iron phosphate (LiFePO4), lithium nickel oxide (LiNiO2), lithium cobalt oxide (LiCoO2), lithium manganese iron phosphate (LiMnPO4), lithium manganese oxide (LiMn2O4) and nickel cobalt manganese ternary positive electrode (LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2).

[0039] Compared with the prior art, the present invention has the following advantages and technical effects:

[0040] (1) The present invention provides a heterogeneous multilayer composite polymer electrolyte, which is composed of an intermediate composite polymer electrolyte, a negative electrode side polymer electrolyte and a positive electrode side gel electrolyte, wherein the intermediate composite polymer electrolyte contains inorganic ceramics, which can not only reduce the crystallinity of the polymer matrix A and improve the ionic conductivity of the electrolyte, but also improve the mechanical properties of the electrolyte and prevent lithium dendrites from damaging the electrolyte.

[0041] (2) The polymer matrix of the negative electrode side polymer electrolyte used in the present invention is polyethylene oxide, which has good thermoplasticity and can be in close contact with the intermediate composite polymer electrolyte after hot pressing. It also has good compatibility and interface compatibility with lithium metal, which is beneficial to optimize the interface contact and reduce the ion transfer impedance.

[0042] (3) The positive electrode side gel electrolyte used in the present invention has the property of transforming from liquid to gel. Its precursor liquid can fully infiltrate the positive electrode and construct a fast ion channel inside the positive electrode. In addition, its gel property optimizes the original solid-solid contact interface, reduces the interface impedance, and promotes the ion transmission of the positive electrode-intermediate composite polymer electrolyte.

[0043] (4) The additives used in the present invention are all Lewis acids, which have multiple functions. In the negative electrode side polymer electrolyte, the basic cations (such as Mg 2+ , Sn 2+ ,In 3+ and Al 3+ ) can easily react with lithium metal in situ to form an artificial SEI layer, which improves the reversibility of lithium ion precipitation / stripping; the alkaline cations in the Lewis acid in the gel electrolyte on the positive electrode side can trigger the ring-opening polymerization of DOL. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0045] Figure 1 The schematic diagram is a structural diagram of a polymer lithium metal battery prepared by using the heterogeneous multilayer composite polymer electrolyte of the present invention.

[0046] Figure 2 This is the test result of the ionic conductivity of the intermediate composite polymer electrolyte in Example 1.

[0047] Figure 3 This is the electrochemical window test result of the intermediate composite polymer electrolyte of Example 2.

[0048] Figure 4 This is the XRD pattern of the intermediate composite polymer electrolyte of Example 3.

[0049] Figure 5 Electrochemical impedance spectroscopy (EIS) test results of the LiFePO4||Li batteries assembled in Examples 1 to 4.

[0050] Figure 6 This is the EIS test result of the LiFePO4||Li battery assembled in Comparative Example 1.

[0051] Figure 7 This is the EIS test result of the LiFePO4||Li battery assembled in Comparative Example 2. DETAILED DESCRIPTION

[0052] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0053] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0054] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0055] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0056] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0057] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0058] All raw materials used in the examples of the present invention are commercially available.

[0059] An embodiment of the present invention provides a heterogeneous multilayer composite polymer electrolyte, which is composed of an intermediate composite polymer electrolyte, a negative electrode side polymer electrolyte and a positive electrode side gel electrolyte, wherein the intermediate composite polymer electrolyte is located between the negative electrode side polymer electrolyte and the positive electrode side gel electrolyte, forming a "sandwich" structure;

[0060] The intermediate composite polymer electrolyte is composed of polymer matrix A, lithium salt and inorganic ceramics, the negative electrode side polymer electrolyte is composed of polymer matrix B, lithium salt and additives, and the positive electrode side gel electrolyte is composed of polymer monomers, lithium salt, solvent and additives.

[0061] The polymer matrix A includes at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-chlorotrifluoroethylene (P(VDF-CTFE)), polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)), polyvinylidene fluoride-trifluoroethylene (P(VDF-TrFE)) and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene (P(VDF-TrFE-CTFE)). The polymer matrix A has a high dielectric constant, can form a higher concentration of free lithium ions, increase the number of lithium ion migration and reduce the activation energy, thereby improving the ionic conductivity of the polymer electrolyte. Using such substances instead of traditional liquid electrolytes has high flexibility, high thermal stability, and a wide electrochemical stability window, thereby improving the electrochemical performance of high-safety and high-specific-energy lithium-ion batteries; and such substances have good interface contact and stronger dissociation ability, can effectively inhibit the growth of lithium dendrites, and improve battery safety;

[0062] The polymer matrix B is polyethylene oxide (PEO). The benefits of using PEO to prepare polymer electrolytes include at least the following: Excellent interfacial contact: PEO-based solid polymer electrolytes show excellent interfacial contact with electrode materials and low interfacial impedance, which is crucial for battery performance. High flexibility: PEO shines in the field of flexible batteries due to its higher flexibility, which can adapt to the volume change of the battery during use. High conductivity: PEO-based polymer electrolytes are considered promising due to their high conductivity and stability. Electrochemical stability: PEO performs well in electrochemical stability and has good chemical compatibility with lithium metal anode, which helps to improve the safety and stability of the battery. Safety: Polymer electrolytes have better high temperature resistance and chemical resistance, and are safer and more reliable than traditional liquid electrolytes. Easy processing: PEO electrolytes have the advantages of good film forming, easy processing and good contact with electrodes to meet different battery design requirements. Improve battery performance and service life: Since polymer electrolytes have the advantages of high conductivity, high mechanical strength and good safety, they can improve the performance and service life of lithium-ion batteries. Inhibiting the growth of lithium dendrites: The polymer electrolyte strategy using PEO matrix as the intermediate layer can inhibit the micro-short circuit of high-safety and high-energy-density batteries caused by the growth of lithium dendrites.

[0063] The polymerized monomer is 1,3-dioxolane (DOL), which has high lithium ion conductivity, good interface contact and low interface resistance, which is crucial to improving battery performance;

[0064] The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), lithium hexafluorophosphate (LiPF6) and lithium difluorooxalatoborate (LiDFOB). The above lithium salts have high lithium ion conductivity and chemical stability, high decomposition temperature and electrochemical window, and can improve the charge and discharge rate and cycle life of the battery, especially the performance at high temperature.

[0065] The mass ratio of lithium salt to polymer matrix A in the intermediate composite polymer electrolyte is 1:30-3:1;

[0066] The mass ratio of lithium salt to polymer matrix B in the negative electrode side polymer electrolyte is 1:30-3:1;

[0067] The mass ratio of lithium salt to polymer matrix in the gel electrolyte on the positive electrode side is 1:30-3:1.

[0068] The inorganic ceramic includes at least one of lithium germanium phosphosulfide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum cerium oxide, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium phosphosulfide, lithium lanthanum titanate, yttria-stabilized zirconium oxide, silicon dioxide, aluminum oxide, titanium dioxide and zirconium dioxide;

[0069] The mass ratio of the inorganic ceramic to the polymer matrix A is 1:50-10:1.

[0070] The additives include at least one of aluminum trifluoromethanesulfonate (Al(OTf)3), lithium tetrafluoroborate (LiBF4), zinc trifluoromethanesulfonate (Zn(OTf)2), tin trifluoromethanesulfonate (Sn(OTf)2), copper trifluoromethanesulfonate (Cu(OTf)2), silver trifluoromethanesulfonate (Ag(OTf)), indium trifluoromethanesulfonate (In(OTf)3), magnesium trifluoromethanesulfonate (Mg(OTf)2), stannous chloride (SnCl2), tin chloride (SnCl4), aluminum iodide (AlI3), aluminum fluoride (AlF3) and aluminum chloride (AlCl3), which can initiate polymerization of polymerization monomers, accelerate active ion transport, improve ion conductivity and reduce interface resistance, enhance the contact between the positive electrode side gel electrolyte and the positive electrode, and help improve battery performance;

[0071] The concentration of the additive in the corresponding electrolyte is 0.0001-5 g / mL.

[0072] The solvent includes at least one of ethylene glycol dimethyl ether (DME), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy) propane (TTE). These solvents have the advantages of high dielectric constant, low viscosity and low price. They can be combined with lithium salts to form electrolytes, provide lithium ion transmission media, and improve battery safety.

[0073] The volume ratio of the solvent to the polymerization monomer is 1:10-10:1.

[0074] The heterogeneous multilayer composite polymer electrolyte in the embodiment of the present invention can be used to prepare a polymer lithium metal battery.

[0075] An embodiment of the present invention further provides a method for preparing a polymer lithium metal battery using a heterogeneous multilayer composite polymer electrolyte, comprising the following steps:

[0076] Add lithium salt and inorganic ceramics to N,N-dimethylformamide and stir for 1-12 hours, then add polymer matrix A and stir for 5-36 hours to obtain A slurry with a solid content of 15-85%, then scrape A slurry on a support plate and place it in a vacuum oven at a temperature of 30-100°C for drying for 10-60 hours, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 70-150 μm;

[0077] Add lithium salt and additives to acetonitrile and stir for 1-12 hours, then add polymer matrix B and mix and stir for 1-36 hours to obtain B slurry with a solid content of 10-85%, then scrape the B slurry on a support plate and place it in a vacuum oven at a temperature of 30-100° C. to dry for 10-60 hours, and cut it to obtain a negative electrode side polymer electrolyte with a thickness of 10-30 μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 40-80° C. and a pressure of 1-100 MPa for 1-120 minutes;

[0078] Add lithium salt and additives to the solvent and stir for 0.1-2h, then add polymerization monomer and mix and stir for 0.01-1h to obtain a positive electrode side gel electrolyte precursor solution, drop the positive electrode side gel electrolyte precursor solution between the positive electrode and the intermediate composite polymer electrolyte, and the positive electrode side gel electrolyte precursor solution is polymerized to form a positive electrode side gel electrolyte to obtain a polymer lithium metal battery.

[0079] In the present invention, the support plate mainly provides a skeleton support so that the polymer electrolyte can be evenly distributed and maintain a certain structure and shape. In an embodiment of the present invention, the support plate is a glass plate.

[0080] In an embodiment of the present invention, the negative electrode is one of metallic lithium, lithium aluminum alloy, lithium silicon alloy, lithium copper alloy, lithium tin alloy, silicon carbon negative electrode, hard carbon negative electrode and graphite.

[0081] In the embodiment of the present invention, the active material of the positive electrode is lithium iron phosphate (LiFePO4), lithium nickel oxide (LiNiO2), lithium cobalt oxide (LiCoO2), lithium manganese iron phosphate (LiMnPO4), lithium manganese oxide (LiMn2O4) and nickel cobalt manganese ternary positive electrode (LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2).

[0082] The structural schematic diagram of the polymer lithium metal battery prepared by using the heterogeneous multilayer composite polymer electrolyte of the present invention is shown in Figure 1 .

[0083] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.

[0084] The technical solution of the present invention is further illustrated by the following embodiments.

[0085] Example 1

[0086] Step 1: In a glove box, add 0.93g LiFSI and 0.14g lithium lanthanum zirconium tantalum oxide to N,N-dimethylformamide and stir for 12h, then add 1.4g P(VDF-CTFE) and mix and stir for 12h to obtain A slurry with a solid content of 25%, then apply A slurry on a support plate and place it in a vacuum oven at 65°C for drying for 36h, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 115μm;

[0087] Step 2: In a glove box, add 1g LiFSI and 0.5g Mg(OTf)2 to acetonitrile and stir for 2h, then add 1g PEO and stir for 12h to obtain B slurry with a solid content of 15%, then scrape the B slurry onto a support plate and place it in a vacuum oven at 50°C for drying for 40h, and cut it to obtain a negative electrode side polymer electrolyte with a thickness of 10μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 50°C and a pressure of 20MPa for 20min, and when assembling a CR2032 button battery, one side of the negative electrode side polymer electrolyte is in contact with the metal lithium negative electrode;

[0088] Step 3: In a glove box, add 0.5g LiFSI and 0.05g Mg(OTf)2 to 1mL DME and 1mL FEC and stir for 0.2h, then add 1mL DOL and mix and stir for 0.1h to obtain a positive electrode side gel electrolyte precursor. When assembling a CR2032 button battery, drop the positive electrode side gel electrolyte precursor between the lithium iron phosphate positive electrode and the intermediate composite polymer electrolyte to form a positive electrode side gel electrolyte. The polymerization time of the positive electrode side gel electrolyte precursor is 72h (polymerization time refers to the time when the positive electrode side gel electrolyte precursor is dropped between the positive electrode and the intermediate composite polymer electrolyte to form a positive electrode side gel electrolyte).

[0089] The ionic conductivity of the intermediate composite polymer electrolyte in this embodiment was tested by electrochemical impedance spectroscopy. The intermediate composite polymer electrolyte was assembled into a stainless steel symmetrical battery. The test range was 10 6 -10 -1 Hz, amplitude is 5mV, test results are shown in Figure 2 It can be seen that the ionic conductivity of the intermediate composite polymer electrolyte in this embodiment is 4.38×10 - 4 S / cm.

[0090] Example 2

[0091] Step 1: In a glove box, add 0.9g LiDFOB and 0.14g lithium lanthanum zirconium oxide to N,N-dimethylformamide and stir for 10h, then add 2.8g P(VDF-HFP) and mix and stir for 24h to obtain A slurry with a solid content of 20%, then apply A slurry on a support plate and place it in a vacuum oven at 60℃ for drying for 30h, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 120μm;

[0092] Step 2: In a glove box, add 0.5g LiDFOB and 0.3g Cu(OTf)2 to acetonitrile and stir for 3h, then add 1.5g PEO and stir for 24h to obtain B slurry with a solid content of 10%, then apply B slurry on a support plate and place it in a vacuum oven at 60°C for drying for 36h, cut to obtain a negative electrode side polymer electrolyte with a thickness of 15μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 55°C and a pressure of 30MPa for 30min, and when assembling a CR2032 button battery, this surface is in contact with the metal lithium negative electrode;

[0093] Step 3: In a glove box, add 0.5g LiDFOB and 0.03g Cu(OTf)2 to 2mL DME and stir for 0.2h, then add 1mL DOL and mix and stir for 0.05h to obtain the positive electrode side gel electrolyte precursor. When assembling CR2032 button batteries, drop the positive electrode side gel electrolyte precursor between the lithium cobalt oxide positive electrode and the intermediate composite polymer electrolyte. The polymerization time of the positive electrode side gel electrolyte precursor is 80h.

[0094] The electrochemical window of the intermediate composite polymer electrolyte in this embodiment is tested by linear voltammetry, the intermediate composite polymer electrolyte is assembled into a lithium||stainless steel battery for testing, and the test voltage range is set to 2.0~6.0V (Li / Li + ), the test rate is 1mV s -1 , test results see Figure 3 It can be seen that the electrochemical window of the intermediate composite polymer electrolyte is about 4.5V.

[0095] Example 3

[0096] Step 1: In a glove box, add 0.67g LiBOB and 0.5g lithium lanthanum zirconium tantalum oxide to N,N-dimethylformamide and stir for 6h, then add 1.4g P(VDF-CTFE) and mix and stir for 20h to obtain A slurry with a solid content of 25%, then apply A slurry on a support plate and place it in a vacuum oven at 50°C for drying for 40h, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 100μm;

[0097] Step 2: In a glove box, add 2g LiBOB and 0.2g Sn(OTf)2 to acetonitrile and stir for 1h, then add 3g PEO and mix and stir for 30h to obtain B slurry with a solid content of 15%, then scrape the B slurry on a support plate and place it in a vacuum oven at a temperature of 60°C for drying for 30h, cut it to obtain a negative electrode side polymer electrolyte with a thickness of 13μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 50°C and a pressure of 25MPa for 30min, and when assembling a CR2032 button battery, this surface is in contact with the lithium aluminum alloy negative electrode;

[0098] Step 3: In a glove box, add 0.7g LiBOB and 0.05g Sn(OTf)2 to 1mL DME and 1mL TTE and stir for 0.2h, then add 1mL DOL and mix and stir for 0.05h to obtain the positive electrode side gel electrolyte precursor. When assembling CR2032 button batteries, drop the positive electrode side gel electrolyte precursor between the lithium cobalt oxide positive electrode and the intermediate composite polymer electrolyte. The polymerization time of the positive electrode side gel electrolyte precursor is 60h.

[0099] The XRD pattern of the intermediate composite polymer electrolyte in this embodiment is shown in Figure 4 It can be seen that the characteristic peak position of lithium lanthanum zirconium tantalum oxide in the intermediate composite polymer electrolyte remains unchanged, indicating that the crystal structure of LLZTO is still a cubic garnet structure.

[0100] Example 4

[0101] Step 1: In a glove box, add 1.34g LiTFSI and 0.5g lithium aluminum titanium phosphate to N,N-dimethylformamide and stir for 5h, then add 1g P(VDF-TrFE-CTFE) and stir for 20h to obtain A slurry with a solid content of 30%, then apply A slurry on a support plate and place it in a vacuum oven at 70°C for drying for 45h, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 120μm;

[0102] Step 2: In a glove box, add 1.5g LiTFSI and 0.5g In(OTf)3 to acetonitrile and stir for 5h, then add 2g PEO and mix and stir for 30h to obtain a B slurry with a solid content of 20%, then scrape the B slurry onto a support plate and place it in a vacuum oven at a temperature of 60°C for drying for 50h, and cut it to obtain a negative electrode side polymer electrolyte with a thickness of 25μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 60°C and a pressure of 30MPa for 30min, and when assembling a CR2032 button battery, this surface is in contact with the metal lithium negative electrode;

[0103] Step 3: In a glove box, add 0.7g LiTFSI and 0.02g In(OTf)3 to 2mL DME and stir for 0.5h, then add 1.5mL DOL and mix and stir for 0.08h to obtain the positive electrode side gel electrolyte precursor. When assembling CR2032 button batteries, add the positive electrode side gel electrolyte precursor dropwise between the lithium iron phosphate positive electrode and the intermediate composite polymer electrolyte. The polymerization time of the positive electrode side gel electrolyte precursor is 48h.

[0104] The electrochemical impedance spectroscopy (EIS) of the LiFePO4||Li battery assembled in Example 1 to Example 4 was tested by electrochemical alternating current impedance spectroscopy, with a test range of 10 6 -10 -1 Hz, amplitude is 5mV, the results are shown in Figure 5 It can be seen that the interface impedance of Example 1 is the smallest, and the interface impedance of Example 3 is the largest.

[0105] Example 5

[0106] Step 1: In a glove box, add 0.5g LiFSI and 0.4g lithium aluminum germanium phosphate to N,N-dimethylformamide and stir for 5h, then add 1.2g PVDF and mix and stir for 25h to obtain A slurry with a solid content of 30%, then scrape A slurry on a support plate and place it in a vacuum oven at 60°C for drying for 36h, and cut to obtain an intermediate composite polymer electrolyte with a thickness of 110μm;

[0107] Step 2: In a glove box, add 0.5g LiFSI and 0.1g AlCl3 to acetonitrile and stir for 5h, then add 2g PEO and mix and stir for 20h to obtain B slurry with a solid content of 10%, then scrape the B slurry on a support plate and place it in a vacuum oven at a temperature of 45°C for drying for 36h, and cut it to obtain a negative electrode side polymer electrolyte with a thickness of 15μm; hot press the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte at a temperature of 45°C and a pressure of 50MPa for 10min, and when assembling a CR2032 button battery, this surface is in contact with the metal lithium negative electrode;

[0108] Step 3: In a glove box, add 1g LiFSI and 0.05g AlCl3 to 1mL DME and stir for 0.5h, then add 2mL DOL and mix and stir for 0.04h to obtain the positive electrode side gel electrolyte precursor. When assembling CR2032 button batteries, drop the positive electrode side gel electrolyte precursor between the lithium iron phosphate positive electrode and the intermediate composite polymer electrolyte. The polymerization time of the positive electrode side gel electrolyte precursor is 65h.

[0109] Comparative Example 1

[0110] Step 1: In a glove box, add 0.93g LiFSI and 0.14g lithium lanthanum zirconium tantalum oxide to N,N-dimethylformamide and stir for 12h, then add 1.4g P(VDF-CTFE) and mix and stir for 12h to obtain A slurry with a solid content of 25%, then apply A slurry on a support plate and place it in a vacuum oven at 65°C for drying for 36h, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 115μm;

[0111] Step 2: In a glove box, hot press the lithium iron phosphate positive electrode sheet and the intermediate composite polymer electrolyte at a temperature of 50°C and a pressure of 20MPa for 20 minutes. When assembling a CR2032 button battery, this surface is in contact with the metal lithium negative electrode;

[0112] Step 3: In the glove box, when assembling a CR2032 button cell, drop LB-002 (1M LiPF6 in DMC:EC:EMC=1:1:1Vol%) liquid electrolyte between the metal lithium negative electrode and the intermediate composite polymer electrolyte.

[0113] The EIS of the LiFePO4||Li battery assembled in this comparative example was tested (the test process is the same as that of Examples 1 to 4), and the test results are shown in Figure 6 It can be seen that the interface impedance of comparative example 1 is greater than the interface impedance of embodiments 1 to 4.

[0114] Comparative Example 2

[0115] Step 1: In a glove box, add 0.93g LiFSI and 0.14g lithium lanthanum zirconium tantalum oxide to N,N-dimethylformamide and stir for 12h, then add 1.4g P(VDF-CTFE) and mix and stir for 12h to obtain A slurry with a solid content of 25%, then apply A slurry on a support plate and place it in a vacuum oven at 65°C for drying for 36h, and cut it to obtain an intermediate composite polymer electrolyte with a thickness of 115μm;

[0116] Step 2: In a glove box, hot press the lithium iron phosphate positive electrode sheet and the intermediate composite polymer electrolyte at a temperature of 50°C and a pressure of 20MPa for 20 minutes. When assembling a CR2032 button battery, this surface is in contact with the metal lithium negative electrode;

[0117] Step 3: In the glove box, when assembling a CR2032 button cell, directly contact the metallic lithium anode with the intermediate composite polymer electrolyte.

[0118] The EIS of the LiFePO4||Li battery assembled in this comparative example was tested (the test process is the same as that of Examples 1 to 4), and the test results are shown in Figure 7 It can be seen that the interface impedance of comparative example 2 is greater than the interface impedance of comparative example 1.

[0119] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A heterogeneous multilayer composite polymer electrolyte, characterized in that: It is composed of an intermediate composite polymer electrolyte, a negative electrode side polymer electrolyte and a positive electrode side gel electrolyte, wherein the intermediate composite polymer electrolyte is located between the negative electrode side polymer electrolyte and the positive electrode side gel electrolyte; The intermediate composite polymer electrolyte is composed of polymer matrix A, lithium salt and inorganic ceramics, the negative electrode side polymer electrolyte is composed of polymer matrix B, lithium salt and additives, and the positive electrode side gel electrolyte is composed of polymer monomers, lithium salt, solvent and additives.

2. The heterogeneous multilayer composite polymer electrolyte according to claim 1, characterized in that: The polymer matrix A is at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-chlorotrifluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene; and / or The polymer matrix B is polyethylene oxide; and / or The polymerizable monomer is 1,3-dioxolane; and / or The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium hexafluorophosphate and lithium difluorooxalatoborate.

3. The heterogeneous multilayer composite polymer electrolyte according to claim 2, characterized in that: The mass ratio of the lithium salt to the polymer matrix A in the intermediate composite polymer electrolyte is 1:30-3:1; and / or The mass ratio of the lithium salt in the negative electrode side polymer electrolyte to the polymer matrix B is 1:30-3:1; and / or The mass ratio of the lithium salt to the polymer matrix in the positive electrode side gel electrolyte is 1:30-3:

1.

4. The heterogeneous multilayer composite polymer electrolyte according to claim 1, characterized in that: The inorganic ceramic is selected from at least one of lithium germanium phosphosulfide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum cerium oxide, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium phosphosulfide, lithium lanthanum titanate, yttria-stabilized zirconium oxide, silicon dioxide, aluminum oxide, titanium dioxide and zirconium dioxide; and / or The mass ratio of the inorganic ceramic to the polymer matrix A is 1:50-10:

1.

5. The heterogeneous multilayer composite polymer electrolyte according to claim 1, characterized in that: The additive is selected from at least one of aluminum trifluoromethanesulfonate, lithium tetrafluoroborate, zinc trifluoromethanesulfonate, tin trifluoromethanesulfonate, copper trifluoromethanesulfonate, silver trifluoromethanesulfonate, indium trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, stannous chloride, tin chloride, aluminum iodide, aluminum fluoride and aluminum chloride; and / or The concentration of the additive in the corresponding electrolyte is 0.0001-5 g / mL.

6. The heterogeneous multilayer composite polymer electrolyte according to claim 1, characterized in that: The solvent is selected from at least one of ethylene glycol dimethyl ether, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, fluoroethylene carbonate and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane; and / or The volume ratio of the solvent to the polymerization monomer is 1:10-10:

1.

7. Use of the heterogeneous multilayer composite polymer electrolyte according to any one of claims 1 to 6 in the preparation of a polymer lithium metal battery.

8. A method for preparing a polymer lithium metal battery using the heterogeneous multilayer composite polymer electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: Adding lithium salt and inorganic ceramics to N,N-dimethylformamide, stirring evenly, then adding polymer matrix A, stirring evenly, obtaining A slurry with a solid content of 15-85%, scraping the A slurry on a support plate and drying, to obtain an intermediate composite polymer electrolyte; Adding lithium salt and additives to acetonitrile, stirring evenly, then adding polymer matrix B, stirring evenly, obtaining B slurry with a solid content of 10-85%, scraping the B slurry on a support plate and drying, scraping the B slurry on a support plate and drying, to obtain a negative electrode side polymer electrolyte; Hot pressing the negative electrode side polymer electrolyte and the intermediate composite polymer electrolyte to form a composite material, and assembling a battery, wherein one side of the negative electrode side polymer electrolyte in the composite material is in contact with the negative electrode; Add lithium salt and additives to the solvent, stir evenly, then add polymerization monomer, stir evenly to obtain a positive electrode side gel electrolyte precursor solution, drop the positive electrode side gel electrolyte precursor solution between the positive electrode and the intermediate composite polymer electrolyte, and polymerize the positive electrode side gel electrolyte precursor solution to form a positive electrode side gel electrolyte to obtain the polymer lithium metal battery.

9. The method according to claim 8, characterized in that The negative electrode is one of metallic lithium, lithium aluminum alloy, lithium silicon alloy, lithium copper alloy, lithium tin alloy, silicon carbon negative electrode, hard carbon negative electrode and graphite.

10. The method according to claim 8, characterized in that The active material of the positive electrode is one of lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide, lithium manganese iron phosphate, lithium manganese oxide and nickel-cobalt-manganese ternary positive electrode.

Citation Information

Patent Citations

  • Composite solid electrolyte, all-solid-state lithium ion battery and preparation method of all-solid-state lithium ion battery

    CN111697262A

  • Solid electrolyte composite layer and lithium ion battery

    CN112599850A

  • In-situ preparation and application of polymer solid electrolyte

    CN114430064A

  • Asymmetric solid electrolyte and preparation method thereof as well as solid lithium battery and preparation method thereof

    CN114614079A

Cited By

  • Preparation method of double-layer composite electrolyte membrane, double-layer composite electrolyte membrane and solid-state battery

    CN121688072A

  • Polymer composite solid electrolyte, battery and preparation method thereof

    CN121885749A